On Sums of a Random Number of Random Multi-Dimensional Vectors - Paulauskas, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Паулаускас. О сумме случайного числа многомерных случайных векторов V. Paulauskas. Apie atsitiktinio skaičiaus atsitiktinių daugiamačių vektorių sumas